355 Primary melanoma of cervix. A case report in colombian population. (18th September 2019) - Santana, D; Caicedo, L; Trujillo, L; Calderon, P; Pareja, R
Abstract : Objectives: Primary mucosal melanoma accounts for 1% of all cancers, presentation in the cervix is rare, there are few cases reported in the literature, the data are limited in staging and treatment, their prognosis is poor. We present a clinical case of 82-year-old colombian patient with a diagnosis of primary melanoma of cervix, the pathological diagnosis was made with immunohistochemistry HMB-45 and S100 are positive in tumor tissue. Methods: Report of 1 clinical case of 82-year-old patient diagnosed with primary melanoma of the cervix Results: Mucous melanoma is more frequent in elderly patients older than 60 years. The etiology of this entity is not clear, there is only hypothesis of the origin, it is presented with non-specific symptoms of vaginal bleeding or flow, macroscopically it presents as an exophytic lesion, pigmented in the cervix, it is necessary for an immunohistochemical diagnosis, for its treatment the surgical approach as the best strategy, there are reports of chemotherapy plans, radiotherapy is reserved for symptomatic palliative control. There are studies for the use of immunotherapy in the management of this pathology with unpromising results. The cervix presentation is aggressive and its prognosis is poor due to the rapid dissemination within a few months of the diagnosis. Conclusions: Primary melanoma of the cervix is a rare entity, even without clear knowledge of its origin, with little evidence of its management and with a poor prognosis of short-term survival.